2019
DOI: 10.18632/aging.102181
|View full text |Cite
|
Sign up to set email alerts
|

Cortical neurons develop a senescence-like phenotype promoted by dysfunctional autophagy

Abstract: Senescent cells accumulate in various tissues and organs with aging altering surrounding tissue due to an active secretome, and at least in mice their elimination extends healthy lifespan and ameliorates several chronic diseases. Whether all cell types senesce, including post-mitotic cells, has been poorly described mainly because cellular senescence was defined as a permanent cell cycle arrest. Nevertheless, neurons with features of senescence have been described in old rodent and human brains. In this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
98
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 52 publications
8
98
1
Order By: Relevance
“…Therefore, we verified that PCNs underwent senescence and proteostasis failure during LTC. We confirmed that, as with PHNs, PCNs exhibited the conventional senescent phenotypes—SA‐β‐gal activity (Moreno‐Blas et al, ; Piechota et al, ), p16 upregulation, lamin B1 reduction, and SASP induction ( Cxcl1 , Igfbp2 , and Igfbp4 )—as well as elevated levels of nuclear REST (Piechota et al, ) by LTC (~ 28 DIV; Figure a–d). These cells also exhibited proteostasis failure, as demonstrated by the accumulation of insoluble Ub‐conjugates (Figure e).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Therefore, we verified that PCNs underwent senescence and proteostasis failure during LTC. We confirmed that, as with PHNs, PCNs exhibited the conventional senescent phenotypes—SA‐β‐gal activity (Moreno‐Blas et al, ; Piechota et al, ), p16 upregulation, lamin B1 reduction, and SASP induction ( Cxcl1 , Igfbp2 , and Igfbp4 )—as well as elevated levels of nuclear REST (Piechota et al, ) by LTC (~ 28 DIV; Figure a–d). These cells also exhibited proteostasis failure, as demonstrated by the accumulation of insoluble Ub‐conjugates (Figure e).…”
Section: Resultssupporting
confidence: 79%
“…We observed robust BafA‐dependent punctate p62 signals at 7 and 14 DIV, indicating an active autophagic flux (Figure g, h). In contrast, the BafA‐dependent signal was less pronounced at 21 DIV and was eventually lost at 28 DIV (Figure g, h), suggesting that the autophagic activity becomes impaired over time in vitro as recently reported in senescence‐like PCNs at 26 DIV (Moreno‐Blas et al, ). Together, these results suggest that proteostasis failure occurred in LTC‐PHNs as evidenced by accumulation of poly‐Ub proteins and amyloid aggregates.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Although later expanded to oncogene-induced senescence (OIS) and stress-induced premature senescence (SIPS), the dogma has persisted that neurons are spared from senescence as they do not apply to the basal concepts of the paradigm. Such a view has now been challenged by the discovery that terminally differentiated neurons acquire a senescence-like phenotype as assessed by different markers, such as SA-β-Gal, 4-HNE, γH2AX, mH2A, p-p38, IL-6, and MCP-1 [2,3]. The appearance and features of cellular senescence in postmitotic or rarely dividing tissues, a phenotype recently termed 'postmitotic cellular senescence' (PoMiCS) [4] and that we here specify as 'amitosenescence' particularly for postmitotic neurons, has been demonstrated in several cell populations, including neuronal cells in tissues of the central nervous system (CNS) [2], cardiomyocytes, osteocytes, and adipocytes [5][6][7].…”
mentioning
confidence: 99%
“…Whether a corresponding SASP in neurons might elicit a canonical or rather alternative factor profile, is still ill-defined. In favor of a highly cell type-specific SASP response, both senescent-like cortical neurons and cardiomyocytes apparently differ in their profile of SASP-associated components secreted, as Edn3, Tgfb2, and Gdf15 have been highlighted for cardiomyocytes [5], whereas GATA4 and MCP-1 were identified to support the SASP in cortical neurons [3]. Interestingly, in both senescent-like postmitotic cell entities classical SASP components, such as IL-1α and IL-1β, were not significantly involved [3,5].…”
mentioning
confidence: 99%